Delivery of a national prenatal exome sequencing service in England: a mixed methods study exploring healthcare professionals’ views and experiences - Peter, Michelle; Mellis, Rhiannon; McInnes-Dean, Hannah; Daniel, Morgan; Walton, Holly; Fisher, Jane; Leeson-Beevers, Kerry; Allen, Stephanie; Baple, Emma L.; Beleza-Meireles, Ana; Bertoli, Marta; Campbell, Jennifer; et al. (Frontiers in Genetics, 2024)
Introduction: In October 2020, rapid prenatal exome sequencing (pES) was introduced into routine National Health Service (NHS) care in England, requiring the coordination of care from specialist genetics, fetal medicine (FM) and laboratory services. This mixed methods study explored the experiences of professionals involved in delivering the pES service during the first two years of its delivery in the NHS. Methods: A survey (n = 159) and semi-structured interviews (n = 63) with healthcare professionals, including clinical geneticists, FM specialists, and clinical scientists (interviews only) were used to address: 1) Views on the pES service; 2) Capacity and resources involved in offering pES; 3) Awareness, knowledge, and educational needs; and 4) Ambitions and goals for the future. Results: Overall, professionals were positive about the pES service with 77% rating it as Good or Excellent. A number of benefits were reported, including the increased opportunity for receiving actionable results for parental decision-making, improving equity of access to genomic tests and fostering close relationships between FM and genetics departments. Nonetheless, there was evidence that the shift to offering pES in a clinical setting had brought some challenges, such as additional clinic time, administrative processes, perceived lack of autonomy in decision-making regarding pES eligibility and difficulty engaging with peripheral maternity units. Concerns were also raised about the lack of confidence and gaps in genomics knowledge amongst non-genetics professionals -especially midwives. However, the findings also highlighted value in both FM, obstetric and genetics professionals benefiting from further training with a focus on recognising and managing prenatally diagnosed genetic conditions. Conclusion: Healthcare professionals are enthusiastic about the benefits of pES, and through multi-collaborative working, have developed relationships that have contributed to effective communication across specialisms. Although limitations on resources and variation in knowledge about pES have impacted service delivery, professionals were hopeful that improvements to infrastructure and the upskilling of all professionals involved in the pathway would optimise the benefits of pES for both parents and professionals.